2022
DOI: 10.3390/ijms23169061
|View full text |Cite
|
Sign up to set email alerts
|

How Hydroxyurea Alters the Gut Microbiome: A Longitudinal Study Involving Angolan Children with Sickle Cell Anemia

Abstract: Sickle cell anemia (SCA) is an inherited hematological disorder and a serious global health problem, especially in Sub-Saharan Africa. Although hydroxyurea (HU) is the leading treatment for patients with SCA, its effects on the gut microbiome have not yet been explored. In this context, the aim of this study was to investigate this association by characterizing the gut microbiome of an Angolan SCA pediatric population before and after 6 months of HU treatment. A total of 66 stool samples were obtained and sequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…In previous papers from our research group, we have proved the existence of notable microbial differences between SCA patients and healthy controls [ 39 ] and have also reported that SCA children before HU treatment had a higher abundance of the pathogenic Clostridium_g24 , whereas after HU, it was observed higher proportions of several beneficial bacteria, mostly short-chain fatty acids (SCFAs) producing species [ 40 ]. This last study was the first evidence of hydroxyurea’s positive effect on the gut microbiome.…”
Section: Discussionmentioning
confidence: 90%
“…In previous papers from our research group, we have proved the existence of notable microbial differences between SCA patients and healthy controls [ 39 ] and have also reported that SCA children before HU treatment had a higher abundance of the pathogenic Clostridium_g24 , whereas after HU, it was observed higher proportions of several beneficial bacteria, mostly short-chain fatty acids (SCFAs) producing species [ 40 ]. This last study was the first evidence of hydroxyurea’s positive effect on the gut microbiome.…”
Section: Discussionmentioning
confidence: 90%
“…First, due to small sample sizes, we were unable to reconcile our microbiota findings with the different treatment modalities in ET. We have previously shown that patients with PV treated with interferon-alpha have a gut microbiota more similar to HCs compared with patients with PV not treated with interferon-alpha ( 25 ), and treatment with hydroxyurea has recently been reported to be associated with an increase in the abundance of beneficial bacteria, such as Faecalibacterium in children with sickle cell anemia ( 39 ). Furthermore, the number of JAK2V617F- negative patients with ET was small (limiting the statistical power) and heterogeneous with other mutations ( CALR and MPL ) or triple negative.…”
Section: Discussionmentioning
confidence: 99%
“…Our ndings are consistent with a study on the use of hydroxyurea in sickle cell disease and its impact on the gut microbiota, which also showed a higher abundance of bene cial bacteria belonging to phyla Firmicutes. (12) The highly abundant genera in the responder's group are mostly butyrate producers from phylum Firmicutes that are bene cial to the host gut. Butyrate, a Short-chain fatty acid (SCFA) is the main source of energy for colonocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the participants were Balochi (20%), Sindhi (20%), and Urdu-speaking (17%). The median of transfusion per year six months after hydroxyurea therapy in responders group was zero with IQR (0-5), and in nonresponder group was 12 per year with IQR (12)(13)(14)(15)(16)(17)(18)(19)(20). Most participants were using Deferasirox as an Ironchelator (53.3%), out of which the majority were HNR (73.3%) and HNU (73.3%).…”
Section: Patient Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation